1988
DOI: 10.1073/pnas.85.12.4305
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of foreign genes into intact maize cells with high-velocity microprojectiles

Abstract: This report describes a process for delivering foreign genes into maize cells that does not require the removal of cell walls and is capable of delivering DNA into embryogenic and nonembryogenic tissues. Plasmid harboring a chimeric chloramphenicol acetyltransferase (CAT) gene was adsorbed to the surface of microscopic tungsten particles (microprojectiles). These microprojectiles were then accelerated to velocities sufficient for penetrating the cell walls and membranes ofmaize cells in suspension culture. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
7

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(104 citation statements)
references
References 13 publications
3
94
0
7
Order By: Relevance
“…The first technique especially developed for the transformation of plant cells and that is also applicable for the transformation of P. patens, is the particle or gene gun technology that delivers DNA biolistically directly into diverse plant tissues (Klein et al, 1988). The biolistic transformation method is not restricted to specific plants or tissue types and functions with the same efficiency in monocotyledonous and dicotyledonous plants (Sawahel et al, 1992).…”
Section: Biolistic Delivery Of Dnamentioning
confidence: 99%
“…The first technique especially developed for the transformation of plant cells and that is also applicable for the transformation of P. patens, is the particle or gene gun technology that delivers DNA biolistically directly into diverse plant tissues (Klein et al, 1988). The biolistic transformation method is not restricted to specific plants or tissue types and functions with the same efficiency in monocotyledonous and dicotyledonous plants (Sawahel et al, 1992).…”
Section: Biolistic Delivery Of Dnamentioning
confidence: 99%
“…Previous work based on the analysis of transient gene expression has shown that microprojectiles can be used for the delivery of DNA to a wide range of intact plant cells and tissues including those from onion, maize, tobacco (13)(14)(15)(16), rice, wheat, and soybean (22). Stable transformation by particle bombardment has been shown in tobacco (16) and soybean (18).…”
mentioning
confidence: 99%
“…Biolistic gene transfer, a method by which foreign genes may be introduced into cells via high velocity microprojectiles (Klein et al 1988) has been used in transforming monocots such as orchids (Suwanaketchanatit et al 2007) and dicots such as soybean (El-Shemy et al 2007), but has only recently been used in potato. Up to 0.5 transformants per leaf shot were achieved using particle bombardment (Craig et al 2005), almost two orders of magnitude higher than the first report in potato .…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%